Use of Clarifying and Disinfecting Agents of Natural Origin for Comprehensive Water Treatment Characterized by Thermal Floors - Ramírez Arcila, Hildebrando; Jaramillo, Jhoan (Ingeniería Solidaria, 2014)
The article presents a methodology that will be used for the research project approved by the Research Development Committee (Comité para el Desarrollo de la Investigación, Conadi) in 2014, entitled “Potential Use of Clarifying And Disinfecting Agents of Natural Origin for Comprehensive Water Treatment Characterized by Thermal Floors” (“Uso potencial de agentes clarificantes y desinfectantes de origen natural para el tratamiento integral del agua caracterizado por pisos térmicos”), which is being carried out through the Civil Engineering program at the Ibagué campus of the Universidad Cooperativa de Colombia. The experimental and comparative research will evaluate and characterize natural agents derived from seeds, leaves, bark or sap, roots and fruits according to their thermal floor (hot, temperate, cold), in terms of their usefulness for comprehensive water treatment. The aim is to provide a method to enable the population to manage, become familiar with and determine potential agents that can fulfill water clarification and disinfection conditions. Until now, 16 seeds have been characterized by thermal floors and according to their respective function as coagulants or disinfectants. The aim is to obtain a databank with the different types of natural agents studied that would show their efficacy and efficiency in water treatment, to subsequently create a natural compound that would combine two agents, a coagulant and a disinfectant, and which would provide a comprehensive solution for communities.